The crusade of Varna and the relations between Jan Hunyadi and Alfons V of Aragon, King of Naples. Reality and ideology - Denize, Eugen (Balcanica Posnaniensia. Acta et studia, 1997)
The article is devoted to the relations between John Hunyadi and Alfonso V of Aragon in the context of the Varna Crusade and the ideology of the struggle against the Turks in the fifteenth century. The author analyzes the clash of political interests between the states of Southeastern Europe and the western Christian monarchies under the banner of the anti-Ottoman crusade. The aim of the study is to present the nature of cooperation between Hunyadi and Alfonso V and to assess the limitations of this cooperation. The author bases the analysis on diplomatic sources and historiography concerning Mediterranean policy and anti-Turkish struggles. The article demonstrates that for the Balkan states the crusade was primarily defensive in character and constituted a struggle to preserve independence, whereas for the western powers it also served as an instrument of political and economic expansion. John Hunyadi sought to create a common front of Central and Eastern European states against the Turks, while Alfonso V treated the idea of crusade as an element of his own Mediterranean policy and his plans to gain influence in the Mediterranean basin and in Constantinople. The results of the analysis indicate that conflicting interests among the partners of the Christian coalition significantly limited the possibility of effective anti-Turkish cooperation.